On the Decline of Star Formation during the Evolution of Galaxies - Adelheid Teklu; Rolf-Peter Kudritzki; Klaus Dolag; Rhea-Silvia Remus; Lucas Kimmig (The Astrophysical Journal, 2023)
Cosmological simulations predict that during the evolution of galaxies, the specific star formation rate continuously decreases. In a previous study we showed that generally this is not caused by the galaxies running out of cold gas but rather a decrease in the fraction of gas capable of forming stars. To investigate the origin of this behavior, we use disk galaxies selected from the cosmological hydrodynamical simulation Magneticum Pathfinder and follow their evolution in time. We find that the mean density of the cold gas regions decreases with time. This is caused by the fact that during the evolution of the galaxies the star-forming regions move to larger galactic radii, where the gas density is lower. This supports the idea of inside-out growth of disk galaxies.